O esporte na aula de educação física escolar: o posicionamento dos professores - Sousa, Jefferson Rodrigues de (2012)
The aim of this study was to analyze what the disposition of attitude of Physical Education teachers of elementary school, working in public schools located in the eastern region of the city of São Paulo, belonging to the board of education Leste 2, with subjects like sports and Scholar Physical Education. The research aimed to investigate how school conducts educational processes and practices, aimed at training and education of the individuals involved. The objective of this project was to analyze the present trend in the attitudes of physical education teachers in relation to Physical Education and Sports in school as content of Physical Education. The specific objectives were: to determine whether there is a predominance in the sporting perspective in Physical Education, from how teachers are positioned in relation to their lessons, analyze the roles and values attributed to sports in physical education (education, linked to promoting citizenship, sports performance, health promoters); consider, in light of Critical Theory, sports in the context of the cultural industry, from how teachers establish the link between sports and culture industry, to analyze the education of the body and formation of the individual, with reference to the way teachers are manifested on the physical education at school; to analyze the ambiguity of the sports and as shown in the positioning of the teachers to analyze the role of sports in accordance with the teachers. The instruments developed for this research was a questionnaire to collect personal data of physical education teachers and a range of attitudes in the form of Likert-type propositions. The adopted procedure aimed at verifying the degree of adherence to the sport, with the establishment of correlations subjected to statistical tests. For a more detailed understanding of the phenomenon of sport and attitude scales, the basis for the discussion of the results was Critical Theory. It was intended, finally, the discussion of the role of sports in physical education, which, consequently, allowed the reflection on the role of physical education at school and the school's role in individual formation. The main findings were that teachers tend to use sports as the main content of their lessons, assigning values and roles as related to educational development of students, health promotion and citizenship, respect for rules, linking the sports to the cultural industry. Data analysis indicates that teachers tend to use sport as the main content of their lessons, assigning roles and values linked to the development of students, health promotion and citizenship, respect rules, and established ties with industry cultural. However, it was also found ambivalent attitude, because there is a tendency for teachers to recognize the boundaries of the sport in respect of the formation